The acceptance of Islamic deposit products among non-muslim bank customers in Malaysia / Nurul Afidah Mohamad Yusof ... [et al.] - Mohamad Yusof, Nurul Afidah; Khoo, Siew Teng; Khor, Siew Yi; Teh, Shu Yi; Webster, Ho Min Zhang; Wong, Soon Seng (Universiti Teknologi MARA, Kedah, 2022)
Undeniably, public awareness has increased since the first establishment of Islamic banking in Malaysia in 1983, but the acceptance of Islamic banking products has yet to be at par with its conventional counterpart. The statistics indicate that despite a steady growth in the Islamic banking market share over the years, there is a large gap between the conventional and Islamic banking system. Although the existence of Islamic banking grounded in the demand and need of Muslims to live according to their faith, it has also witnessed a significant by-choice subscription of Islamic banking by non-Muslims. In a multiracial country like Malaysia with an approximate of 40% non-Muslim population, it is especially important to attract the non-Muslim population in order for the Islamic banking to further penetrate the market. Therefore, the objective of this paper is to examine the factors influencing the acceptance of Islamic deposit products among non-Muslim bank customers in Malaysia. A total sample of 303 respondents were surveyed by using online questionnaire, and further analysed by using multiple linear regression. The results indicate that a favourable bank reputation, higher awareness, and higher income level would positively influence the non-Muslim bank customers to subscribe to the Islamic deposit products.